Hubungan Pengetahuan Ibu dengan Perilaku dalam Pengelolaan Sampah Plastik : Di Desa Moncongkomba Kecamatan Polongbangkeng Selatan Kabupaten Takalar Tahun 2023 - Westy Tenriawi (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Environmental pollution caused by plastic waste is increasingly worrying if there is no effort to manage it properly. People who lack knowledge and have bad behavior in managing plastic waste can cause health and environmental problems. This study aims to determine the relationship between the level of knowledge of housewives with the behavior of managing plastic waste. The study was conducted in Monconkomba Village, Posel District, Takalar Regency in 2023. This study used a cross sectional study design, with a sample of 58 people taken by simple random sampling. Data collection was done by structured interviews using a questionnaire. Data were analyzed using univariate analysis and bivariate analysis with the Kai Square (X2) statistical test. The study found about 42.8% of respondents had poor knowledge and about 48.8% of respondents had poor behavior. Bivariate analysis showed a highly significant relationship between the level of knowledge of housewives and the behavior of managing plastic waste. There is a very significant relationship between the level of knowledge of housewives and the behavior of managing plastic waste in Bontolebang Hamlet, Moncongkomba Village, Polsel District, Takalar Regency in 2023.